Application of Cyclic Thermal-Oxidized IrOx Electrode in pH Detection of Zn/Steel Galvanic Process in 3.5 wt.% NaCl Solution. Issue 16 (24th November 2020) - Huang, Feifei; Wang, Qingrui; Bi, Peng; Yu, Zhigang; Wang, Weipeng; Wang, Shuqiang; Wen, Lei; Jin, Ying
Abstract : The IrOx electrodes fabricated by cyclic heating and quenching process show excellent comprehensive properties including wide E-pH range, near Nernst pH sensitivity, fast response rate, and long term stability etc. The IrOx electrodes are applied in the detection of surface pH changes during galvanic corrosion process of zinc/steel couple in 1 mm 3.5 wt.% NaCl electrolyte layer and 3.5 wt.% NaCl bulk solution, respectively. This detection is realized by integrating the self-fabricated IrOx pH sensor and self-assembled moving platform together. Before the application of the IrOx electrode, the appropriate way of scanning the surface of the zinc/steel galvanic couple is discussed. Comparing with the case in bulk solution, the zinc/steel couple corrodes faster in 1 mm electrolyte layer, the surface pH of which increases to a high value after corrosion begins for 20∼40 min, and the low pH region exists on the zinc surface and the region adjacent to border area of the steel surface, whereas the pH value of the steel surface away from the border area is relatively high. It is demonstrated that the IrOx electrode could detect the pH distribution effectively in surface region during metal corrosion, which could help the understanding of corrosion process under different situations.